THE DYNAMICS OF THE STUDY OF TAFSIR IN INDONESIA: TRACING THE JOURNEY OF INDONESIAN INTERPRETATION FROM TIME TO TIME - Nikmah, Shofiatun (Universitas Nurul Jadid, 2021)
The rapid development of the study of interpretation in Indonesia departs from the collective awareness from academics that’s Nusantara Scholars have been trying to develop interpretation products since the beginning. The study of interpretation in Indonesia has cultural acculturation which is interesting. Local language revealed be interpretation language. The aim of the research is to describe comprehensively the dynamics of the development of interpretation in Indonesia in each period, with the use socio-historic approach. And in the form of library research. The result of the research shows that development and research in the studies of interpretation move dynamically and consist of four periods. Namely the Classical period, the medieval period, the pre-modern period, and the modern period.